Service Effectiveness in Enhancing Customer Satisfaction: Evidence from Studio Room Services in Gowa Regency, Indonesia - Nasrullah; Moh.Aris Pasiqai; Muh.Hanif Fatin (Universitas Muhammadiyah Makassar, 2026)
This study investigates the effectiveness of service delivery in enhancing customer satisfaction at Kamar Studio, a small and medium-sized enterprise (SME) operating in the fashion and printing service industry in Gowa Regency, Indonesia. Adopting a qualitative descriptive approach, the research explores how service effectiveness is perceived and experienced by customers through the dimensions of service quality. Data were collected through in-depth interviews, direct observations, and documentation involving the business owner, employees, and customers. The analysis followed an interactive qualitative model encompassing data reduction, data display, and conclusion drawing, supported by triangulation to ensure credibility. The findings reveal that service effectiveness significantly contributes to customer satisfaction across all SERVQUAL dimensions, namely reliability, responsiveness, assurance, empathy, and tangibles. Reliable service delivery, reflected in order accuracy and timely completion, strengthens customer trust and satisfaction. Responsiveness through prompt communication and proactive service updates enhances perceived service value. Assurance, manifested in employee competence and service guarantees, reduces perceived risk and fosters repeat patronage. Empathy creates emotional satisfaction by providing personalized and attentive service experiences, while tangible aspects such as facilities, equipment, and visual presentation reinforce perceptions of professionalism and service credibility. Overall, the study confirms that integrated service effectiveness plays a vital role in shaping positive customer perceptions, encouraging loyalty, repeat purchases, and positive word-of-mouth. These findings highlight the applicability of the SERVQUAL framework within the context of SMEs in creative service industries and offer practical insights for improving service-oriented strategies to support sustainable business growth.